Razvoj ureditve ukrepov zavarovanja v evropskem civilnem procesnem pravu - Pogorelčnik Vogrinc, Neža (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2014)
The question of protecting claims is old; probably it arose shortly after first debts were made. But still the new problems arise constantly at this field, especially when there is an international element involved in the legal relationship in dispute. At the level of the European Union this field has been subject to the regulation for many years, the latest one could be found in Regulation (EU) No. 1215/2012 of the European Parliament and of the Council of 12 December 2012 on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters, which shall apply from 10 January 2015. With the overview of major changes the article tries to show the development of the subject and its influence on the positions of the creditors and debtors.
Keywords: upniki; terjatve; zavarovanje; izvršba; izvršilni postopek; sodne odločbe; pravna ureditev; European Union; Evropska unija